Manual de alimentación adecuada para fortalecer el desarrollo infantil temprano en menores de 3 años, 2019 - Reyes Avalos, Laura Lizet (2020)
In this research, an adequate feeding manual is proposed considering that timely feeding can strengthen early childhood development in children under 3 years. It is also about promoting the idea that a well-nourished child without anemia grows strong, healthy, cheerful, and performs more in school in the future. A well-fed child becomes less sick with diarrhea or respiratory infection and saves the cost of caring for these diseases and in the treatment of anemia. Meanwhile, early childhood development in children under 3 years of age implies that each child has their own rhythm and some capacities are gradually being built, in this sense development is a continuous process that occurs when the child interacts with people, this means that a child has life, health and good nutrition as part of his well-being and as a basis for development. An environment conducive to its integral development. The idea of investigating in the study variables such as: early childhood feeding and development, has allowed me to propose a feeding manual aimed at parents in order to create healthy habits and thereby establish assertive behaviors regarding the development of attitudes to be architects of sustainable development based on an adequate habit of eating practices of their minor children.